A self-assessment study of procedural skills of doctors in peri-urban district hospitals of Gauteng, South Africa - Neetha J. Erumeda; Ian D. Couper; Leena S. Thomas (AOSIS, 2019)
Background: Several studies have been carried out on procedural skills of doctors in district hospitals in rural South Africa. However, there is insufficient information about skills of doctors in peri-urban district hospitals. This paper attempts to supplement this vital information. Aim: The aim of the study was to determine self-reported levels of competence in procedural skills of doctors in peri-urban district hospitals and to assess factors influencing this. Setting: The study was undertaken in three district hospitals in two health districts of Gauteng Province. Methods: A cross-sectional descriptive study using a self-administered questionnaire was undertaken in three district hospitals in two health districts of Gauteng Province. The questionnaire assessed procedural skills based on district health service delivery requirements for doctors in district hospitals using a modified skill set developed for family medicine training in South Africa. Results: There was a wide range of self-reported competence and experience among doctors for various skill sets. Doctors were generally more competent for procedures in general surgery, medicine, orthopaedics, obstetrics and gynaecology and paediatrics than anaesthesia, ear, nose and throat and ophthalmology. There were statistically significant associations between age and overall anaesthetic competence (p = 0.03); gender and overall competence in surgery (p = 0.03), orthopaedics (p = 0.02) and urology (p = 0.005); years of experience and overall competence in dermatology skills; current hospital and overall competence in anaesthesia (p = 0.01), obstetrics and gynaecology (p = 0.015) and dermatology skills (p = 0.01). Conclusion: This was one of the first studies to look at self-reported procedural competence of doctors in a peri-urban setting in South Africa. The results highlight the need for regular skills audits, standardised training and updating of skills of doctors in district hospitals.